KEARIFAN LOKAL DALAM TRADISI MECAH PARUK DI DESA ARJOWINANGUN, KECAMATAN PURING, KABUPATEN KEBUMEN (PERSPEKTIF ISLAM) - Lina Aniqoh (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2018)
Tradition as a local wisdom of an area becomes part of ancestral cultural heritage that is important to be preserved and its meaning explored. Broken tradition in the village of Arjowinganun, Puring, Kebumen is a slametan pregnancy tradition of two or more women who have brotherly ties. This tradition has seven main symbols, namely Friday, wingka, crossroads, krawu gedhang raja, muddy lumbu, paruk and split up. The seven symbols that after interpreting their meaning using Victor Turner’s symbol interpretation theory revealed that each symbol has noble values and moral messages that are in harmony with Islamic teachings. Broken traditions are generally held on Friday located at crossroads. The practice of this tradition is the sale and purchase menu of ready-to-eat food consisting of white rice, krawu gedhang raja, muddy lumbu and complementary side dishes with banana leaf wrappers, a means of paying legitimate sale and purchase transactions namely wingka or stone. Alignment of moral messages in the tradition of breaking up with Islamic teachings is found in the teachings of always praying and praying for good, being a person who is moral, useful, has a high social spirit, draws closer to God and gives advice to charity.